PENGARUH CORPORATE SOCIAL RESPONSIBILITY, UKURAN PERUSAHAAN, PROFITABILITAS, LEVERAGE, CAPITAL INTENSITY DAN KEPEMILIKAN KELUARGA TERHADAP AGRESIVITAS PAJAK (Studi Empiris Pada Perusahaan Pertambangan dan Pertanian yang terdaftar di Bursa Efek Indonesia P - Mustika '; Vince Ratnawati; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine the effect of corporate social responsibility, size of firm, profitability, leverage, capital intensity and family ownership to tax aggressiveness in mining and agricultural companies listed in the Indonesia StockExchange. The research data is secondary data in the form of the annual reports of companies. While the population in this study are all mining and agricultural companies listed in the Indonesia Stock Exchange during 2012-2014. Selection ofthe sample using purposive sampling method in which the population of 63 selected according to criteria of a sample of 13 companies selected. The data analysis used is multiple regression. The results of this study show that corporatesocial responsibility has positive effect on the tax aggressiveness with significant value of 0,028, size of firm no effect on the tax aggressiveness with significant value of 0,641, profitability no effect on the tax aggressiveness with significant value of 0,393, leverage no effect on the tax aggressiveness with significant value of 0,897, capital intensity no effect on the tax aggressiveness with significant value of 0,946, and family ownership has negative effect on the tax aggressiveness with significant value of 0,021. The coefficient of determination in this study 0,11 shows that 11% of the variations that occur in the tax aggressiveness is affectedby corporate social responsibility, size of firm, profitability, leverage, capital intensity, as well as the family ownership and the remaining 89% is influenced by other variables not included in this research.Keyword : Corporate Social Responsibility, Size Of Firm, Profitability, Leverage, and Tax Aggressiveness